Using Shadowing Technique to Improve Listening Skill of Grade Eleven Students at MAN 2 Parigi - Salma Cinta, Yobli; Jamiluddin, Jamiluddin; Hasyim, Zarkiani; Kamaruddin, Abd (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
The primary objective of this research was to investigate the effectiveness of the shadowing technique in improving the listening skills of eleventh-grade students at MAN 2 Parigi. Using a quasi-experimental design, the study compared two groups: an experimental group that received listening instruction through shadowing and a control group that received conventional instruction. Assessment tools consisted of pre- and post-tests with multiple-choice and fill-in-the-blank items designed to evaluate micro and macro listening skills. The findings revealed substantial improvement in the listening performance of the experimental group after the intervention. Their mean score increased significantly from 43.33 on the pretest to 84.17 on the posttest. In contrast, the control group showed only a marginal increase, from 27.59 to 39.66. Statistical analysis using the Mann-Whitney U test revealed a significance value of 0.000, confirming a statistically significant difference between the two groups. Based on this result, the null hypothesis was rejected in favor of the alternative hypothesis. Therefore, it can be concluded that the shadowing technique significantly improves the listening skills of eleventh-grade students at MAN 2 Parigi.